2015
DOI: 10.1016/j.foodchem.2014.08.068
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of ultrasound-assisted extraction of oil from papaya seed by response surface methodology: Oil recovery, radical scavenging antioxidant activity, and oxidation stability

Abstract: The present study aimed to investigate the effects of ultrasound-assisted extraction (UAE) condition on the yield, antioxidant activity and stability of the oil from papaya seed. The studied ultrasound variables were time, temperature, ultrasound power and solvent to sample ratio. The main goal was to optimise UAE condition providing the highest recovery of papaya seed oil with the most desirable antioxidant activity and stability. The interaction of ultrasound variables had the most and least significant effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
157
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(185 citation statements)
references
References 31 publications
12
157
1
6
Order By: Relevance
“…For the three factors, the Box-Behnken design was chosen since it offers advantages in requiring a fewer number of runs. Results showed that the yield ranged from 3.60 to 8.25% and the maximum extraction yield of olive oil from ultrasound assisted extraction was obtained at higher temperatures and longer malaxation times as reported by several researchers (Angerosa et al, 2001;Inarejos-García et al, 2009;Samaram et al, 2015;Taticchi et al, 2013). These values were relatively lower than the values reported by Clodoveo et al, (2013) and Jimenez et al, (2007).…”
Section: Fitting the Response Surface Methodsmentioning
confidence: 56%
See 2 more Smart Citations
“…For the three factors, the Box-Behnken design was chosen since it offers advantages in requiring a fewer number of runs. Results showed that the yield ranged from 3.60 to 8.25% and the maximum extraction yield of olive oil from ultrasound assisted extraction was obtained at higher temperatures and longer malaxation times as reported by several researchers (Angerosa et al, 2001;Inarejos-García et al, 2009;Samaram et al, 2015;Taticchi et al, 2013). These values were relatively lower than the values reported by Clodoveo et al, (2013) and Jimenez et al, (2007).…”
Section: Fitting the Response Surface Methodsmentioning
confidence: 56%
“…2d-f) 3D response surface plots were created. According to the results, a higher amount of oil was obtained by the ultrasound extraction at elevated ultrasound temperatures for longer malaxation time which could confirm that the ultrasound extraction at higher temperatures could disintegrate the cell wall and membranes, and promote the mass transfer from olive fruit (Samaram et al, 2015). However, the ultrasound time applied in the extraction had no significant effect on the yield (Figures2a and 2b).…”
Section: Fitting the Response Surface Methodsmentioning
confidence: 73%
See 1 more Smart Citation
“…The advantage of flash extraction is rapid and efficient that the extraction time is extremely short and generally less than 3 min. The extraction time for conventional reflux extraction and ultrasonic-assisted extraction range from one to several hours and 30-60 minutes, respectively, with the extraction rate higher than 95 25 . Cold pressing provides high quality edible oil without hexane residues since its toxicity has been demonstrated 24 , but the extraction yield is only 40-80 .…”
Section: Effects Of Ash Extraction Parameters On Oil Yieldmentioning
confidence: 99%
“…When many factors and interactions may affect a desired response, the RSM is an effective tool to find the optimal conditions for process (Stroescu et al, 2013). RSM is very popular for optimization solid-liquid extraction in recent years (Liu et al, 2009;Samaram et al, 2015). RSM is a statistical technique used to design experiments to obtain relevant information in the shortest possible time at the lowest cost.…”
Section: Introductionmentioning
confidence: 99%